Speaking with the People's Voice : How Presidents Invoke Public Opinion - Drury, Jeffrey P. Mehltretter, 1979- (Book collections on Project MUSE., 2014)
The role of public opinion in American democracy has been a central concern of scholars who frequently examine how public opinion influences policy makers and how politicians, especially presidents, try to shape public opinion. But in Speaking with the People's Voice: How Presidents Invoke Public Opinion, Jeffrey P. Mehltretter Drury asks a different question that adds an important new dimension to the study of public opinion: How do presidents rhetorically use public opinion in their speeches? In a careful analysis supported by case studies and discrete examples, Drury develops the concept of invoked public opinion to study the modern presidents' use of public opinion as a rhetorical resource. He defines the term as the rhetorical representation of the beliefs and values of US citizens. Speaking with the People's Voice considers both the strategic and democratic value of invoked public opinion by analyzing how modern presidents argumentatively deploy references to the beliefs and values of US citizens as persuasive appeals as well as acts of political representation in their nationally televised speeches.